Social networking in Mexico: a reflection - Azuela-Flores, José Ignacio (Universidad Autónoma de Tamaulipas, 2011)
In just over five years, the number of sites dedicated to social networks as the number of users have grown considerably. Coupled with this growth, the viral nature of the information on these sites is shared highly attractive for business. Perhaps, from the point of view of marketing, the main attraction of these sites is that they’re considered a channel of communication with the market. While it is true that social networks can be used to establish bilateral communication between company and consumer, is also true that they are an ideal place for communication between consumers. This feature and its enormous potential as an instrument of marketing which makes them particularly attractive. This essay offers a brief approach to the phenomenon of social networking sites in Mexico.